Interfaith Learning Innovations: Strategies Used by PAI-PAK Teachers to Foster Religious Moderation Among Students at SMAN 01 Pecangaan - Nasfi, Naila Tazkiyatan; Saefudin, Ahmad (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2026)
The growing exposure of students to radical and intolerant ideologies presents a challenge for fostering social cohesion in pluralistic societies such as Indonesia. This study examines how Islamic Religious Education (PAI) and Christian Religious Education (PAK) teachers collaborate to implement pedagogical strategies that strengthen students' religious moderation in a diverse school context. Using a qualitative case study design, data were collected through interviews, observations, and document analysis involving school leaders, teachers, and students at a public senior high school in Jepara. The data were analyzed using thematic analysis. The findings show that religious moderation emerges from the interaction of four key elements: institutional policies and leadership support, interfaith teacher collaboration, interactive learning strategies, and students' daily social interactions. These elements form a Collaborative Moderation Model, in which moderation is internalized as a systemic and relational process rather than a single instructional outcome. This study contributes an integrated framework for promoting religious moderation and provides practical implications for developing inclusive educational practices in pluralistic settings.